Modified silicon-based negative electrode material, preparation method thereof and lithium ion battery containing modified silicon-based negative electrode material

By doping with various elements and coating with carbon, a modified silicon-based negative electrode material was prepared, which solved the conductivity and stability problems of silicon-based negative electrode materials in lithium-ion batteries, and significantly improved the first efficiency and rate performance of the battery. and cyclic stability.

CN119340381APending Publication Date: 2025-01-21BEIJING IAMETAL NEW ENERGY TECH CO LTD +2

Patent Information

Application Number
CN202310907601.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-21
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

Silicon-based negative electrode materials have problems such as low first effect, low conductivity, and large volume expansion in lithium-ion batteries, resulting in limited room for improvement of battery energy density and poor rate performance and cycle stability.

Method used

By doping Group IA elements, Group IIA elements and other group elements, and coating them with carbon, a modified silicon-based negative electrode material is prepared, which improves its electronic conductivity and ionic conductivity, suppresses side reactions between lithium and silicon, and enhances the material. structural stability.

Benefits of technology

Modified silicon-based anode materials significantly improve the first efficiency, rate performance and cycle stability of lithium-ion batteries, and solve the conductivity and stability problems of traditional silicon-based anode materials under high-rate conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119340381A_ABST
    Figure CN119340381A_ABST
Patent Text Reader

Abstract

The invention provides a modified silicon-based negative electrode material, a preparation method thereof and a lithium ion battery containing the modified silicon-based negative electrode material. The modified silicon-based negative electrode material comprises an inner core and a carbon coating layer coating the inner core, the chemical formula of the inner core is AaEeMmSiOx; the element A is selected from Li, Na, K, Rb and Cs; the element E is selected from the group consisting of Be, Mg, Ca, Sr and Ba; element M is selected from the group consisting of B, Al, Ga, In, Tl, Ge, Sn, Pb, N, P, As, Sb, Bi, S, Se, Te, F, Cl, Br, and I. The modified silicon-based negative electrode material provided by the invention has good electronic conductivity and ionic conductivity, can inhibit the side reaction of lithium and silicon during lithium intercalation, is stable in structure, and can improve the first effect, rate capability and cycling stability of the lithium ion battery at the same time when being applied to the lithium ion battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of lithium ion batteries, and in particular relates to a modified silicon-based negative electrode material, a preparation method thereof and a lithium ion battery comprising the same. Background Art

[0002] With the rapid development of economy, energy crisis and environmental problems are becoming more and more serious. Lithium-ion batteries have been widely used in pure electric vehicles, hybrid electric vehicles and energy storage due to their advantages of high energy density, high power density, long cycle life, safety and reliability, and environmental friendliness.

[0003] At present, commercial lithium-ion batteries mainly use graphite as the negative electrode material, and the specific capacity of high-end graphite materials on the market has reached the theoretical limit, so the corresponding lithium-ion battery energy density has limited room for improvement. Silicon-based negative electrode materials have a high theoretical specific capacity (4200mAh / g) and a low electrochemical lithium insertion potential. Using them to replace graphite negative electrodes is expected to significantly improve the energy density of lithium-ion batteries, which is also an urgent need for the development of a series of new technology fields such as new energy vehicles and energy storage battery systems.

[0004] However, silicon-based negative electrodes still have the following problems: 1) Silicon-based negative electrode materials are prone to form lithium silicate compounds when lithium is first inserted. The lithium in the compound cannot be reversibly removed, resulting in a low first efficiency of the battery, which is not conducive to the improvement of the energy density of the whole battery; 2) In addition, the intrinsic conductivity and ionic conductivity of silicon-based negative electrode materials are low. Although their conductivity can be improved by carbon coating, the overall electronic conductivity and ionic conductivity of silicon-based negative electrode materials are not high, which is not conducive to their charge and discharge cycles under high rate conditions; 3) Carbon-coated silicon-based negative electrode materials still have problems such as volume expansion that cannot be ignored, making silicon-based negative electrode materials easy to break and shatter after multiple cycles, which is not conducive to long-cycle stability. In response to the above problems, CN106654194B, CN115084530B, and CN110556529A all improve the rate performance or first efficiency of silicon-based negative electrode materials by doping, but they cannot take both into account at the same time.

[0005] Therefore, how to overcome the above-mentioned shortcomings of silicon-based negative electrode materials to simultaneously improve the first efficiency, rate performance and cycle stability of lithium-ion batteries using silicon-based negative electrodes is a problem that needs to be urgently solved in this field. Summary of the invention

[0006] In view of the shortcomings of the prior art, the present invention aims to provide a modified silicon-based negative electrode material, a preparation method thereof and a lithium-ion battery comprising the same. The modified silicon-based negative electrode material has good electronic conductivity and ionic conductivity, can inhibit the side reaction of lithium and silicon during lithium insertion, and has a stable structure. When used in a lithium-ion battery, it can simultaneously improve the first efficiency, rate performance and cycle stability of the lithium-ion battery.

[0007] To achieve this object, the present invention adopts the following technical solutions:

[0008] In a first aspect, the present invention provides a modified silicon-based negative electrode material, wherein the modified silicon-based negative electrode material comprises a core and a carbon coating layer coating the core;

[0009] The chemical formula of the core is A a E e M m SiO x ;

[0010] Wherein, element A is selected from one or more of Li, Na, K, Rb and Cs;

[0011] The element E is selected from one or more of Be, Mg, Ca, Sr and Ba;

[0012] The element M is selected from one or more of B, Al, Ga, In, Tl, Ge, Sn, Pb, N, P, As, Sb, Bi, S, Se, Te, F, Cl, Br and I;

[0013] 0.1≤a≤1 (for example, it can be 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9 or 1.0, etc.),

[0014] 0≤e≤0.15 (for example, it can be 0, 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.1, 0.11, 0.12, 0.13, 0.14 or 0.15, etc.),

[0015] 0.01≤m≤0.15 (for example, it can be 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.1, 0.11, 0.12, 0.13, 0.14 or 0.15, etc.),

[0016] 0<x<2 (for example, it can be 0.1, 0.2, 0.3, 0.4, 0.5, 0.55, 0.6, 0.65, 0.7, 0.75, 0.8, 0.85, 0.9, 0.95, 1, 1.05, 1.1, 1.15, 1.2, 1.25, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8 or 1.9, etc.).

[0017] The modified silicon-based negative electrode material provided by the present invention is prepared by using elements of the periodic table IA group (Li, Na, K, Rb, Cs), IIA group (Be, Mg, Ca, Sr, Ba), IIIA group (B, Al, Ga, In, Tl), IVA group (Ge, Sn, Pb), VA group (N, P, As, Sb, Bi), VIA group (S, Se, Te), VIIA group (F, Cl, Br, I) to modify the silicon-based negative electrode material SiO x It is obtained by doping and carbon coating.

[0018] The incorporation of the above-mentioned Group IA elements and Group IIA elements helps to improve the ionic conductivity of silicon-based negative electrode materials and inhibit the side reaction of lithium and silicon during lithium insertion, thereby improving the first efficiency of the battery. At the same time, Group IIA elements can also improve the stability of silicon-based negative electrode materials, but their effect on improving the first efficiency of the battery is worse than that of Group IA elements; the incorporation of Group IIIA, Group IV, Group VA, Group VIA, and Group VIIA elements helps to improve the electronic conductivity, ionic conductivity, and internal bonding strength of silicon-based negative electrode materials. When the modified silicon-based negative electrode material obtained by co-doping with the above-mentioned elements is used in lithium-ion batteries, it can simultaneously improve the first efficiency, rate performance, and cycle stability of lithium-ion batteries.

[0019] In some embodiments of the present invention, the element A is selected from one or more of Li, Na and K.

[0020] In some embodiments of the present invention, the element E is selected from one or more of Mg, Ca, Sr and Ba.

[0021] In some embodiments of the present invention, the element M is selected from one or more of B, Al, Ge, In, Sn, N, P, S, F, Cl and Br. In some embodiments of the present invention, 0.3≤a≤0.9, 0.02≤e≤0.1, 0.02≤m≤0.1, 0.5≤x≤1.3.

[0022] In some embodiments of the present invention, the content of the carbon coating layer in the modified silicon-based negative electrode material is 2-6wt%; for example, it can be 2wt%, 2.2wt%, 2.5wt%, 2.8wt%, 3wt%, 3.2wt%, 3.5wt%, 3.8wt%, 4wt%, 4.2wt%, 4.5wt%, 4.8wt%, 5wt%, 5.2wt%, 5.5wt%, 5.8wt% or 6wt%, etc.

[0023] In a second aspect, the present invention provides a method for preparing the modified silicon-based negative electrode material as described in the first aspect, the preparation method comprising the following steps:

[0024] (1) Silicon-based negative electrode material SiO x , mixing the E source and the M source, and then vacuum evaporating to obtain a first intermediate product;

[0025] (2) cooling and crushing the first intermediate product, and then carbon coating the first intermediate product to obtain a second intermediate product;

[0026] (3) The second intermediate product is mixed with source A, and then calcined to obtain the modified silicon-based negative electrode material.

[0027] It should be noted that the A source, E source, and M source in the present invention refer to precursors containing element A, element E, and element M, respectively. Those skilled in the art will readily understand that if the modified silicon-based negative electrode material contains impurities, it will have an adverse effect on the performance of the battery, so the A source, E source, and M source preferably do not contain impurity elements that cannot be removed by calcination.

[0028] In some embodiments of the present invention, the E source and the M source in step (1) are respectively selected from one or more of the simple substance, oxide, hydroxide, carbonate, nitrate, sulfate, organic acid salt, metal compound and non-metal compound of element E and element M.

[0029] It should be noted that not every element E and element M in the present invention can be doped in any of the above-mentioned precursor forms. For a specific element, those skilled in the art can select a precursor form suitable for doping according to the properties of its precursor. For element E, its compound precursor may contain only one element E, or contain multiple elements E at the same time, or contain element E and element M at the same time; for element M, its compound precursor may contain only one element M, or contain multiple elements M at the same time, or contain element E and element M at the same time. When the precursor contains element E and element M at the same time, it is both an E source and an M source (such as MgCl2). In the present invention, if the E source and the M source contain oxygen, the oxygen atom will not be doped into the final product.

[0030] In some embodiments of the present invention, the vacuum degree of the vacuum evaporation in step (1) is 2-100Pa, for example, it can be 2Pa, 5Pa, 8Pa, 10Pa, 15Pa, 20Pa, 25Pa, 30Pa, 40Pa, 50Pa, 60Pa, 70Pa, 80Pa, 90Pa or 100Pa, etc.; the temperature of the heating end is 1100-1500℃, for example, it can be 1100℃, 1120℃, 1150℃, 1180℃, 1200℃, 1220℃, 1250℃, 1280℃, 1300℃, 1320℃, 1350℃, 1380℃, 1400℃, 1420℃, 1450℃, 1480℃ or 1500℃, etc.

[0031] In the present invention, there is no particular limitation on the cooling temperature and the pulverizing method in step (2). For example, the cooling temperature may be 0-50° C., and the pulverizing method may be ball milling or air flow pulverizing.

[0032] In some embodiments of the present invention, the carbon coating in step (2) is gas phase carbon coating.

[0033] In some embodiments of the present invention, the gas-phase carbon coating includes: calcining the first intermediate product for a first time in a first gas carbon source atmosphere, and calcining it for a second time in a second gas carbon source atmosphere; the decomposition temperature of the second gas carbon source is higher than the decomposition temperature of the first gas carbon source, and the temperature of the second calcination is higher than the temperature of the first calcination.

[0034] In some embodiments of the present invention, the first gaseous carbon source is selected from one or more of toluene, benzene, methyl acrylate and acetylene, the temperature of the first calcination is 500-900°C (for example, it can be 500°C, 520°C, 550°C, 580°C, 600°C, 620°C, 650°C, 680°C, 700°C, 720°C, 750°C, 780°C, 800°C, 820°C, 850°C, 880°C or 900°C), and the time is 1-8h (for example, it can be 1 h, 2h, 3h, 4h, 5h, 6h, 7h or 8h, etc.); the second gaseous carbon source is selected from one or more of ethylene, methane, ethane, propane and butane, the temperature of the second calcination is 800-1000°C (for example, it can be 800°C, 820°C, 850°C, 880°C, 900°C, 920°C, 950°C, 980°C or 1000°C, etc.), and the time is 1-8h (for example, it can be 1h, 2h, 3h, 4h, 5h, 6h, 7h or 8h, etc.).

[0035] By using two gaseous carbon sources for two-step carbon coating, the carbon coating can be made more complete and the coating integrity can be improved.

[0036] In some embodiments of the present invention, the source A in step (3) is selected from one or more of a single substance, a hydride and an active organic compound of element A. These substances can react with SiOx to form an irreversible silicate compound, thereby reducing the loss of active lithium during the first cycle of the battery and improving the first coulombic efficiency of the battery.

[0037] In some embodiments of the present invention, step (3) is: mixing the second intermediate product with source A, a co-solvent and an organic solvent, heating at 20-60°C (for example, 20°C, 25°C, 30°C, 35°C, 40°C, 45°C, 50°C, 55°C or 60°C, etc.) for 2-10h (for example, 2h, 3h, 4h, 5h, 6h, 7h, 8h, 9h or 10h, etc.), solid-liquid separation, vacuum drying the solid product, and 400-900°C (for example, The modified silicon-based negative electrode material is calcined at 400°C, 420°C, 450°C, 480°C, 500°C, 520°C, 550°C, 580°C, 600°C, 620°C, 650°C, 680°C, 700°C, 720°C, 750°C, 780°C, 800°C, 820°C, 850°C, 880°C or 900°C for 2-12h (for example, 2h, 3h, 4h, 5h, 6h, 7h, 8h, 9h, 10h, 11h or 12h, etc.) to obtain the modified silicon-based negative electrode material.

[0038] In the above liquid phase treatment, the A source can be complexed with the co-solvent, thereby being fully and evenly mixed with the second intermediate product, so that the element A is evenly doped in the second intermediate product during the subsequent calcination process.

[0039] In some embodiments of the present invention, step (3) is: ball milling the second intermediate product and source A in a protective atmosphere for 2-8h (for example, it can be 2h, 3h, 4h, 5h, 6h, 7h or 8h, etc.), and then calcining at 300-700℃ (for example, it can be 300℃, 350℃, 400℃, 450℃, 500℃, 550℃, 600℃, 650℃ or 700℃, etc.) in a protective atmosphere for 3-15h (for example, it can be 3h, 4h, 5h, 6h, 7h, 8h, 9h, 10h, 11h, 12h, 13h, 14h or 15h, etc.) to obtain the modified silicon-based negative electrode material.

[0040] In the present invention, there is no particular limitation on the protective atmosphere. For example, the protective atmosphere may be a nitrogen atmosphere, an argon atmosphere, or the like.

[0041] In some embodiments of the present invention, the molar ratio of the A source to the co-solvent is 1-20:1; for example, it can be 1:1, 2:1, 3:1, 4:1, 5:1, 6:1, 8:1, 10:1, 12:1, 13:1, 15:1, 16:1, 18:1 or 20:1, etc.

[0042] In some embodiments of the present invention, the co-solvent is selected from one or more of biphenyl, naphthalene, anthracene, phenanthrene and dimethylbiphenyl. In the present invention, the co-solvent can complex with element A to promote the dissolution of the A source.

[0043] In some embodiments of the present invention, the organic solvent is selected from one or more of tetrahydrofuran, silicone oil, benzene, toluene and diethyl ether.

[0044] In a third aspect, the present invention provides a negative electrode plate, comprising the modified silicon-based negative electrode material as described in the first aspect.

[0045] In a fourth aspect, the present invention provides a lithium-ion battery, comprising the negative electrode sheet as described in the third aspect.

[0046] Compared with the prior art, the present invention has the following beneficial effects:

[0047] The modified silicon-based negative electrode material provided by the present invention is doped with a variety of elements and carbon-coated, wherein the incorporation of group IA elements and group IIA elements improves the ionic conductivity of the silicon-based negative electrode material and can inhibit the side reaction of lithium and silicon during lithium insertion; the incorporation of group IIIA, group IV, group VA, group VIA, and group VIIA elements improves the electronic conductivity, ionic conductivity, and bonding strength of the silicon-based negative electrode material. When the modified silicon-based negative electrode material is used in a lithium-ion battery, the rate performance, first efficiency, and cycle stability of the lithium-ion battery can be improved at the same time. BRIEF DESCRIPTION OF THE DRAWINGS

[0048] Figure 1 The voltage-capacity relationship curve of the first charge and discharge of a lithium-ion battery using the modified silicon-based negative electrode material provided in Example 1 of the present invention is shown. DETAILED DESCRIPTION

[0049] The technical solution of the present invention is further described below with reference to the accompanying drawings and through specific implementations. It should be understood by those skilled in the art that the specific implementations are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0050] Example 1

[0051] This embodiment provides a modified silicon-based negative electrode material, comprising a core and a carbon coating layer covering the core; the chemical formula of the core is Li 0.553 Sn 0.037SiO, the content of the carbon coating layer is about 3.2wt%.

[0052] The preparation method of the modified silicon-based negative electrode material in this embodiment is as follows:

[0053] (1) 7 g of silicon dioxide (SiO) powder and 0.7 g of metallic tin were added to a ball mill (the mass ratio of the material to the zirconium ball (grinding bead) was 1:10) and mixed evenly, and then the material was loaded into a vacuum evaporation furnace, the heating end temperature was 1300° C., the collecting end temperature was 700° C., the vacuum degree was 5 Pa, and the vacuum evaporation was performed for 10 h to obtain a first intermediate product;

[0054] (2) Cooling the first intermediate product to 50° C. and then ball milling it; adding the obtained powder to a nitrogen-protected tubular furnace, heating it, and when the temperature reaches 800° C., introducing toluene gas into the furnace for calcination, with a gas flow rate of 3 L / min and a ventilation time of 60 min; then switching the gas to nitrogen, heating it, and when the temperature reaches 900° C., introducing ethylene gas into the furnace for calcination, with a gas flow rate of 3 L / min and a ventilation time of 60 min, to obtain a second intermediate product;

[0055] (3) 0.609 g of lithium metal sheet, 1.353 g of biphenyl and the second intermediate product were added to 40 mL of tetrahydrofuran, mechanically stirred for 30 min, and heated in an oil bath at 50 ° C for 6 h after being mixed evenly, filtered, and the solid product was vacuum dried, and then calcined at 750 ° C for 6 h in a nitrogen atmosphere to obtain the modified silicon-based negative electrode material, D 50 The particle size is about 6.4μm.

[0056] Example 2

[0057] This embodiment provides a modified silicon-based negative electrode material, which differs from the embodiment 1 only in that metallic sodium is used in step (3) instead of metallic lithium, and the chemical formula of the core is Na 0.168 Sn 0.037 SiO.

[0058] Example 3

[0059] This embodiment provides a modified silicon-based negative electrode material, which is different from Embodiment 1 only in that the co-solvent used in step (3) is naphthalene.

[0060] Example 4

[0061] This embodiment provides a modified silicon-based negative electrode material, which is different from the embodiment 1 only in that step (3) is:

[0062] 0.609 g of metallic lithium powder and the second intermediate product were ball-milled and mixed for 2 h, and the mixed material was calcined at 450° C. for 4 h in a nitrogen atmosphere to obtain the modified silicon-based negative electrode material.

[0063] Example 5

[0064] This embodiment provides a modified silicon-based negative electrode material, which is different from the embodiment 1 only in that the amount of metal tin used in step (1) is 0.5 g, and the chemical formula of the core is Li 0.553 Sn 0.026 SiO.

[0065] Example 6

[0066] This embodiment provides a modified silicon-based negative electrode material, which is different from the embodiment 1 only in that in step (1), 7 g of silicon dioxide (SiO) powder, 0.4 g of metal Sn and 0.3 g of metal Mg are added to a ball mill (the mass ratio of the material to the zirconium ball is 1:10) and mixed evenly, and the remaining steps are the same as the embodiment 1. The chemical formula of the core is Li 0.553 Mg 0.077 Sn 0.021 SiO.

[0067] Example 7

[0068] This embodiment provides a modified silicon-based negative electrode material, which is different from the embodiment 1 only in that in step (1), 7 g of silicon dioxide (SiO) powder, 0.7 g of MgO and 0.7 g of In2O3 are added to a ball mill (the mass ratio of the material to the zirconium ball is 1:10) and mixed evenly, and the remaining steps are the same as the embodiment 1. The chemical formula of the core is Li 0.553 Mg 0.108 In 0.032 SiO.

[0069] Example 8

[0070] This embodiment provides a modified silicon-based negative electrode material, which is different from the embodiment 1 only in that in step (1), 7 g of silicon dioxide (SiO) powder, 0.5 g of CaO and 0.5 g of P2O5 are added to a ball mill (the mass ratio of the material to the zirconium ball is 1:10) and mixed evenly, and the remaining steps are the same as the embodiment 1. The chemical formula of the core is Li 0.553 Ca 0.057 P 0.045 SiO.

[0071] Example 9

[0072] This embodiment provides a modified silicon-based negative electrode material, which is different from the embodiment 1 only in that in step (1), 7 g of silicon dioxide (SiO) powder, 0.6 g of calcium oxalate and 0.6 g of BF3 are added to a ball mill (the mass ratio of the material to the zirconium ball is 1:10) and mixed evenly, and the remaining steps are the same as the embodiment 1. The chemical formula of the core is Li 0.553 Ca0.03 B 0.039 F 0.117 SiO.

[0073] Example 10

[0074] This embodiment provides a modified silicon-based negative electrode material, which is different from the embodiment 1 only in that in step (1), 7 g of silicon oxide (SiO) powder, 0.5 g of tin oxide and 0.5 g of SrSeO4 are added to a ball mill (the mass ratio of the material to the zirconium ball is 1:10) and mixed evenly, and the remaining steps are the same as the embodiment 1. The chemical formula of the core is Li 0.553 Sr 0.014 Sn 0.024 Se 0.014 SiO.

[0075] Comparative Example 1

[0076] This comparative example provides a modified silicon-based negative electrode material, which differs from Example 1 only in that step (3) is not performed, and the second intermediate product is used as the modified silicon-based negative electrode material, and the chemical formula of the core is Sn 0.037 SiO.

[0077] Comparative Example 2

[0078] This comparative example provides a modified silicon-based negative electrode material, and its preparation method is as follows:

[0079] (1) 7 g of silicon dioxide (SiO) powder was added to a nitrogen-protected tubular furnace, and the temperature was raised. When the temperature reached 800° C., toluene gas was introduced into the furnace for calcination, with a gas flow rate of 3 L / min and a ventilation time of 60 min; then the gas was switched to nitrogen, and the temperature was raised. When the temperature reached 900° C., ethylene gas was introduced into the furnace for calcination, with a gas flow rate of 3 L / min and a ventilation time of 60 min, to obtain carbon-coated silicon dioxide;

[0080] (2) 0.609 g of lithium metal sheet, 1.353 g of biphenyl and the carbon-coated silicon oxide were added to 40 mL of tetrahydrofuran, mechanically stirred for 30 min, and heated in an oil bath at 50 ° C for 6 h after being mixed evenly, filtered, and the solid product was vacuum dried, and then calcined at 750 ° C for 6 h in a nitrogen atmosphere to obtain a modified silicon-based negative electrode material, the chemical formula of the core of which is Li 0.553 SiO.

[0081] Electrochemical performance test:

[0082] The modified silicon-based negative electrode material, Super P (conductive carbon black), and PAA (polyacrylic acid) binder provided in the above embodiments and comparative examples were added into deionized water at a mass ratio of 80:10:10 to form a slurry. The slurry was coated onto a copper foil with a 100 μm thick scraper, dried in a drying room, and vacuum dried for 6 h to prepare a negative electrode sheet with an area density of 1 mg / cm 2 ; Then, a metal lithium sheet (300 μm thick) was used as the counter electrode, polyethylene as the separator, and 1 mol / L LiPF6 solution (the solvent was a mixture of ethylene carbonate and dimethyl carbonate in a volume ratio of 1:1, and the solution contained 2% VC (vinylene carbonate) and 5% FEC (fluoroethylene carbonate) by volume) as the electrolyte, and a button cell was assembled in an argon atmosphere glove box.

[0083] The electrochemical performance of the assembled battery was tested on a LAND charge and discharge tester. The test method is as follows:

[0084] First effect: discharge the battery to 0.005V at 0.1C, let it stand for 5 minutes, then discharge it to 0.005V at 0.05C, let it stand for 5 minutes, and finally discharge it to 0.005V at 0.02C, and then charge it to 1.5V at 0.1C, and test the charge and discharge capacity. First effect = first charge capacity / first discharge capacity;

[0085] Rate performance: The battery was activated 3 times at 0.1C, with the charge and discharge range of 0.005-1.5V, and then charged and discharged at 1C, 2C, and 5C rates to test the discharge specific capacity;

[0086] Cycle performance: The battery was charged and discharged for 80 cycles at 0.5C, with the charge and discharge range of 0.005-1.5V, and the discharge capacity retention rate was calculated.

[0087] The results of the above tests are shown in Table 1 below:

[0088] Table 1

[0089]

[0090] in, Figure 1 The voltage-capacity relationship curve of the first charge and discharge of the lithium-ion battery using the modified silicon-based negative electrode material provided in Example 1 shows that its first charge specific capacity is 1383.34 mAh / g and the first cycle coulomb efficiency is 89.81%.

[0091] It can be seen from the above test results that the lithium-ion battery using the modified silicon-based negative electrode material provided by the present invention has good first efficiency, rate performance and cycle stability. Compared with Example 1, in Comparative Example 1, elemental lithium doping was not performed, and its first efficiency was only 74.84%; in Comparative Example 2, only lithium doping was performed, and although the first efficiency could reach 89.45%, the rate performance and cycle stability of the battery were greatly reduced.

[0092] The above description is only a specific embodiment of the present disclosure, so that those skilled in the art can understand or implement the present disclosure. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present disclosure. Therefore, the present disclosure will not be limited to the embodiments described herein, but will conform to the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A modified silicon-based negative electrode material, characterized in that: The modified silicon-based negative electrode material comprises a core and a carbon coating layer coating the core; The chemical formula of the core is A a E e M m SiO x ; Wherein, element A is selected from one or more of Li, Na, K, Rb and Cs; The element E is selected from one or more of Be, Mg, Ca, Sr and Ba; The element M is selected from one or more of B, Al, Ga, In, Tl, Ge, Sn, Pb, N, P, As, Sb, Bi, S, Se, Te, F, Cl, Br and I; 0.1≤a≤1, 0≤e≤0.15, 0.01≤m≤0.15, 0<x<2.

2. The modified silicon-based negative electrode material according to claim 1, characterized in that: The element A is selected from one or more of Li, Na and K; Preferably, the element E is selected from one or more of Mg, Ca, Sr and Ba; Preferably, the element M is selected from one or more of B, Al, Ge, In, Sn, N, P, S, F, Cl and Br.

3. The modified silicon-based negative electrode material according to claim 1 or 2, characterized in that: 0.3≤a≤0.9, 0.02≤e≤0.1, 0.02≤m≤0.1, 0.5≤x≤1.

3.

4. The modified silicon-based negative electrode material according to any one of claims 1 to 3, characterized in that: The content of the carbon coating layer in the modified silicon-based negative electrode material is 2-6 wt %.

5. A method for preparing a modified silicon-based negative electrode material according to any one of claims 1 to 4, characterized in that: The preparation method comprises the following steps: (1) Silicon-based negative electrode material SiO x , mixing the E source and the M source, and then vacuum evaporating to obtain a first intermediate product; (2) cooling and crushing the first intermediate product, and then carbon coating the first intermediate product to obtain a second intermediate product; (3) The second intermediate product is mixed with source A, and then calcined to obtain the modified silicon-based negative electrode material.

6. The preparation method according to claim 5, characterized in that: In step (1), the E source and the M source are selected from one or more of the simple substance, oxide, hydroxide, carbonate, nitrate, sulfate, organic acid salt, metal compound and non-metal compound of element E and element M respectively; Preferably, the vacuum degree of the vacuum evaporation in step (1) is 2-100 Pa, and the temperature of the heating end is 1100-1500°C.

7. The preparation method according to claim 5 or 6, characterized in that: The carbon coating in step (2) is gas phase carbon coating; Preferably, the gas phase carbon coating comprises: calcining the first intermediate product for the first time in a first gas carbon source atmosphere, and calcining it for the second time in a second gas carbon source atmosphere; the decomposition temperature of the second gas carbon source is higher than the decomposition temperature of the first gas carbon source, and the temperature of the second calcination is higher than the temperature of the first calcination; Preferably, the first gas carbon source is selected from one or more of toluene, benzene, methyl acrylate and acetylene, and the temperature of the first calcination is 500-900°C and the time is 1-8h; the second gas carbon source is selected from one or more of ethylene, methane, ethane, propane and butane, and the temperature of the second calcination is 800-1000°C and the time is 1-8h.

8. The preparation method according to any one of claims 5 to 7, characterized in that: The A source in step (3) is selected from one or more of a simple substance, a hydride and an active organic compound of element A; Preferably, step (3) comprises: mixing the second intermediate product with source A, a co-solvent and an organic solvent, heating at 20-60° C. for 2-10 h, separating the solid and the liquid, and vacuum drying the solid product, and calcining at 400-900° C. for 2-12 h in a protective atmosphere to obtain the modified silicon-based negative electrode material; Alternatively, the second intermediate product and source A are ball-milled in a protective atmosphere for 2-8 hours, and then calcined at 300-700° C. for 3-15 hours in a protective atmosphere to obtain the modified silicon-based negative electrode material; Preferably, the molar ratio of the A source to the cosolvent is 1-20:1; Preferably, the co-solvent is selected from one or more of biphenyl, naphthalene, anthracene, phenanthrene and dimethylbiphenyl; Preferably, the organic solvent is selected from one or more of tetrahydrofuran, silicone oil, benzene, toluene and diethyl ether.

9. A negative electrode plate, characterized in that: It comprises the modified silicon-based negative electrode material as described in any one of claims 1 to 4.

10. A lithium ion battery, characterized in that: Comprising the negative electrode sheet as claimed in claim 9.

Citation Information

Patent Citations

  • An element-doped SiOx anode composite material, its preparation method and application

    CN106654194B

  • Negative electrode composite material with multilayer core-shell structure and preparation method and application thereof

    CN110556529A

  • A high-cycle silicon-based anode material, its preparation method and application

    CN115084530B

Cited By

  • Negative active material and preparation method thereof, solid-state battery and electric equipment

    CN121641908A